Bug Tracker: A Comprehensive Bug Tracking and Modification System - Vasumathi, K.; Selvakani, S.; Sridhar, P. (Asian Journal of Electrical Sciences, 2022)
It is important that information provided in bug reports is relevant and complete in order to help resolve bugs quickly. However, often such information trickles to developers after several iterations of communication between Developers and reporters. Poorly designed bug tracking systems are partly to blame for this exchange of information being stretched over time. Our paper addresses the concerns of bug tracking systems by proposing four broad directions for enhancements. As a proof-of-concept, we also demonstrate a prototype interactive bug tracking system that gathers relevant information from the user and identifies files that need to be fixed to resolve the bug.